Clinical Features of Segmental Infantile Hemangioma: A Prospective Study - Qiu T (Dove Medical Press, 2021)
Tong Qiu,1 Kaiying Yang,1 Shiyi Dai,1 Siyuan Chen,2 Yi Ji1 1Division of Oncology, Department of Pediatric Surgery, West China Hospital of Sichuan University, Chengdu 610041, People’s Republic of China; 2Pediatric Intensive Care Unit, Department of Critical Care Medicine, West China Hospital of Sichuan University, Chengdu 610041, People’s Republic of ChinaCorrespondence: Yi JiDivision of Oncology, Department of Pediatric Surgery, West China Hospital of Sichuan University, #37# Guo-Xue-Xiang, Chengdu 610041, People’s Republic of ChinaFax +86 28 85423453Email jijiyuanyuan@163.comBackground: Infantile hemangioma (IH) is the most common benign tumor in children. However, few studies have reported the clinical features of segmental IH. We aimed to determine the clinical characteristics of segmental IH and to identify features that may aid clinicians in managing segmental IH.Methods: In the cross-sectional prospective study approved by the Ethics Committee of the hospital, children diagnosed with IH were recruited, and information including patient demographics, IH morphology and anatomical location, complications and treatments were recorded and analyzed.Results: In total, 153 patients with segmental IH and 1375 patients with nonsegmental IH were enrolled in this study. The average age on the day of the first visit in patients with segmental IH was 3.63± 3.23 months. In 69 patients (45.10%), segmental IH was diagnosed at birth. Most segmental IHs (49.67%) occurred in the limbs, while only 22.04% of nonsegmental IHs occurred in the extremities (P< 0.001). Thirteen patients (8.50%) with segmental IH had ulceration. Compared with patients with nonsegmental IHs, patients with segmental IHs were more likely to be treated with oral drugs (P< 0.001).Conclusion: Segmental IHs mainly occur in the extremities and are frequently diagnosed at birth. Segmental IHs are usually accompanied by ulceration, which are more commonly seen in the neck and perineal/perianal/genital areas than nonsegmental IHs. Oral propranolol is prescribed more often in patients with segmental IH than in those with nonsegmental IH.Keywords: segmental infantile hemangioma, clinical features, complications, treatment, ulceration